Development and in-vitro evaluation of chitosan and glyceryl monostearate based matrix lipid polymer hybrid nanoparticles (LPHNPs) for oral delivery of itraconazole. Issue 3 (March 2023) - Yousaf, Rimsha; Khan, Muhammad Imran; Akhtar, Muhammad Furqan; Madni, Asadullah; Sohail, Muhammad Farhan; Saleem, Ammara; Irshad, Kanwal; Sharif, Ali; Rana, Maria
Abstract: Itraconazole (ICZ) is a broad spectrum antifungal drug, but used as second or third line therapy due to its low and erratic oral bioavailability. This work was carried out to prepare and characterize matrix type lipid-polymer hybrid nanoparticles (LPHNPs) for dissolution enhancement of ICZ. LPHNPs were prepared using solvent diffusion/emulsification technique. Matrix LPHNPs were composed of chitosan (polymer), glyceryl monostearate (lipid) and poloxamer 188 (stabilizer). LPHNPs loaded with ICZ (LPHNPs-1, LPHNPs-2, LPHNPs-3 and LPHNPs-4) were developed using varying concentration of chitosan whereas LPHNPs (LPHNPs-5, LPHNPs-6, LPHNPs-7 and LPHNPs-8) were prepared using varying concentrations of poloxamer 188. LPHNPs loaded with ICZ were further evaluated for entrapment efficiency, particle size, polydispersity index (PDI), zeta potential and dissolution profiles at biorelevant pH conditions. The particle size (LPHNPs-1 to LPHNPs-4) was found to be in range of 421–588 nm with PDI values 0.34–0.41. The particles size of LPHNPs-5 to LPHNPs-8 was found to be in range of 489–725 nm with PDI 0.34–0.74. The entrapment efficiency of LPHNPs-1 to LPHNPs-4 was found to be in range of 85.21%–91.34%. The entrapment efficiency of LPHNPs-5 to LPHNPs-8 was found to be in range 78.32%–90.44%. . The scanning electron microscopy of optimized formulations LPHNPs-1 and LPHNPs-5 indicated formation of oval shaped nanoparticles. DSC thermogram of ICZ loaded LPHNPs also depicted the conversion of crystalline form of ICZ into amorphous form demonstrating the internalization and dissolution enhancement of drug in the hybrid matrix. The cumulative drug dissolved at acidic pH 1.2 was found to be 23.3% and 19.8% for LPHNPs-1 and LPHNPs-5 respectively. Similarly at basic pH values 7.4, cumulative amount of drug dissolved was 90.2% and 83.4% for LPHNPs-1 and LPHNPs-5 respectively. Drug dissolution kinetics exhibited fickian diffusion best described by Korse-meyer Peppas model. The results suggested that chitosan and glyceryl monostearate based matrix LPHNPs could be used as promising approach for dissolution enhancement of ICZ which could further increase its bioavailability.